2013
DOI: 10.1038/srep01648
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Redox Effect on Gas Permeation of Cobalt Doped Ethoxy Polysiloxane (ES40) Membranes

Abstract: This work reports the remarkable effect of reversible gas molecular sieving for high temperature gas separation from cobalt doped ethoxy polysiloxane (CoES40) membranes. This effect stemmed from alternating the reducing and oxidising (redox) state of the cobalt particles embedded in the ES40 matrix. The reduced membranes gave the best H2 permeances of 1 × 10−6 mol m−2 s−1 Pa−1 and H2/N2 permselectivities of 65. The reduction process tailored a molecular gap attributed to changes in the specific volume between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 36 publications
3
43
2
Order By: Relevance
“…Previous reports explained that redox effect happened because the pore sizes have increased during the reduction process. This was the case for cobalt oxide silica membranes prepared with ES40 silica precursor which has stronger silica backbone branches [13]. However, TEOS was used as the silica precursor in this work, which has a tendency to form weakly branched, fractal structures [39].…”
Section: Fig 1 the Volumetric Adsorption Systemmentioning
confidence: 91%
See 2 more Smart Citations
“…Previous reports explained that redox effect happened because the pore sizes have increased during the reduction process. This was the case for cobalt oxide silica membranes prepared with ES40 silica precursor which has stronger silica backbone branches [13]. However, TEOS was used as the silica precursor in this work, which has a tendency to form weakly branched, fractal structures [39].…”
Section: Fig 1 the Volumetric Adsorption Systemmentioning
confidence: 91%
“…However, cobalt oxide particles embedded in silica films using similar methods as in this work are very small to be detected by XRD (X-ray diffraction). To address this problem, Miller et al [13] recently reported that Co 3 O 4 as Co (III) in silica was reduced to CO (II)…”
Section: Fig 1 the Volumetric Adsorption Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Further development of this concept came about in 2012 for metal oxide silica membranes. Miller et al [4] showed that cobalt oxide silica membranes repeatedly switched the flux of He, CO 2 and N 2 by exposing the membrane to redox conditioning. An interesting aspect of this work was that the metal oxide was constrained by an amorphous silica matrix, though the switching redox effect has not been previously observed for metal oxide silica membranes which underwent extensive research since early 2005.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting aspect of this work was that the metal oxide was constrained by an amorphous silica matrix, though the switching redox effect has not been previously observed for metal oxide silica membranes which underwent extensive research since early 2005. A major reason for this switching effect was attributed to replacing the conventional TEOS silica precursor with ES40, which proved to have superior properties to cope with the switching associated with cobalt phase change in the silica matrix under redox cycling [4].…”
Section: Introductionmentioning
confidence: 99%